Battery and manufacturing method thereof

By providing an isolation layer and a conductive layer in the through hole of the honeycomb structure of the battery, the problem of poor contact caused by drying and shrinking of the positive electrode material is solved, and the internal resistance of the battery is reduced and the conductivity is improved.

JP7626115B2Active Publication Date: 2025-02-04TOYOTA JIDOSHA KK
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022148857
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-09-20
Publication Date
2025-02-04
Estimated Expiration
2042-09-20

AI Technical Summary

Technical Problem

In the existing batteries, the positive electrode material shrinks during drying to form a subsided part, resulting in poor connection between the positive electrode and the positive electrode current collector, which increases the internal resistance of the battery.

Method used

The negative electrode material with a honeycomb structure is adopted. By providing an isolation layer and a conductive layer in the through hole of the honeycomb structure, the conductive layer is connected to the external part of the positive electrode current collector, ensuring that good contact can be maintained even when the positive electrode material shrinks.

Benefits of technology

It effectively reduces the internal resistance of the battery and improves the conductivity and overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626115000002
    Figure 0007626115000002
  • Figure 0007626115000003
    Figure 0007626115000003
  • Figure 0007626115000004
    Figure 0007626115000004
Patent Text Reader

Abstract

To reduce battery resistance.SOLUTION: A battery includes a negative electrode mixture, a separator layer, a positive electrode mixture, a conductive layer, and a positive electrode current collector. The negative electrode mixture forms a honeycomb structure. The honeycomb structure includes a first end face, a second end face, and a side wall. The side wall connects the first end face and the second end face. A plurality of through holes extending from the first end face to the second end face are formed. The separator layer covers at least part of an inner wall of the through hole. The separator layer separates the positive electrode mixture from the negative electrode mixture. The positive electrode mixture is arranged inside the through hole. The conductive layer includes a conductive material. The conductive layer has a composition different from that of the positive electrode mixture. The positive electrode current collector is arranged outside the through hole. The conductive layer connects the positive electrode mixture and the positive electrode current collector.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to batteries and methods for making the same. [Background technology]

[0002] JP 2020-123484 A (Patent Document 1) discloses a first electrode having a plurality of through holes and a second electrode filled in the through holes. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-123484 A Summary of the Invention [Problem to be solved by the invention]

[0004] 1 is an explanatory diagram of a problem in one aspect of the present disclosure. A negative electrode composite material 10 is formed into a predetermined shape. A plurality of through holes 2 are formed in the negative electrode composite material 10. The through holes 2 have a first opening 2a and a second opening 2b. A separator layer 30 covers the inner wall of the through holes 2.

[0005] For example, the positive electrode paste 4 is pressed into the through hole 2 from the first opening 2a. As the positive electrode paste 4 dries, the positive electrode mixture 20 is disposed inside the through hole 2. When the positive electrode paste 4 dries, the positive electrode paste 4 may shrink. As the positive electrode paste 4 shrinks, a depressed portion 21 (dent) may occur in the positive electrode mixture 20. As the depressed portion 21 is formed at the tip of the positive electrode mixture 20, the connection between the positive electrode mixture 20 and the positive electrode current collector 25 becomes insufficient, and the battery resistance may increase.

[0006] An object in one aspect of the present disclosure is to reduce battery resistance. [Means for solving the problem]

[0007] The technical configuration and effects of the present disclosure will be described below. However, the mechanism of action in this specification includes assumptions. The mechanism of action does not limit the technical scope of the present disclosure.

[0008] 1. A battery according to one aspect of the present disclosure includes a negative electrode composite, a separator layer, a positive electrode composite, a conductive layer, and a positive electrode current collector. The negative electrode composite includes a negative electrode active material. The negative electrode composite forms a honeycomb structure. The honeycomb structure includes a first end face, a second end face, and a side wall. The second end face is the opposite face to the first end face. The side wall connects the first end face and the second end face. A plurality of through holes are formed extending from the first end face to the second end face. Each of the through holes has a first opening opening to the first end face and a second opening opening to the second end face. The separator layer covers at least a portion of the inner wall of the through hole. The separator layer separates the positive electrode mixture from the negative electrode mixture. The positive electrode mixture includes a positive electrode active material and is disposed inside the through-hole. The conductive layer includes a conductive material. The conductive layer has a different composition from the positive electrode mixture. The positive electrode current collector is disposed outside the through hole. The conductive layer connects the positive electrode mixture and the positive electrode current collector.

[0009] The battery described in "1" above includes a conductive layer. The conductive layer extends so as to connect the positive electrode mixture inside the through hole and the positive electrode current collector outside the through hole. Therefore, even if a recess is formed at the tip of the positive electrode mixture, the positive electrode mixture and the positive electrode current collector can be connected. This is expected to reduce the battery resistance.

[0010] 2. In the battery according to the above item "1," a conductive layer may be disposed so as to cover at least one of the first opening and the second opening.

[0011] The conductive layer is formed so as to cover the opening, and it is expected that the conductive layer will fill the recessed portion. The conductive layer is expected to fill the recessed portion, and thus the resistance between the positive electrode mixture and the positive electrode current collector will be reduced.

[0012] 3. In the battery according to the above item "1" or "2," the positive electrode mixture may include a recessed portion that recesses from the first opening or the second opening toward the inside of the through hole.

[0013] 4. In the battery according to any one of the above items "1" to "3," the conductive material may include, for example, at least one selected from the group consisting of spherical carbon particles, disk-shaped carbon particles, and rod-shaped carbon particles.

[0014] 5. In the battery according to any one of the above items "1" to "4," the conductive material may have an equivalent sphere diameter of, for example, 10 μm or more.

[0015] For example, when a conductive paste is applied, if the conductive material penetrates into the separator layer, a short circuit may be formed. When the conductive material has a sphere-equivalent diameter of 10 μm or more, the conductive material tends to have difficulty penetrating into the separator layer.

[0016] 6. In the battery according to any one of the above items 1 to 5, the conductive layer may further contain a binder. The mass ratio of the binder to the conductive material may be, for example, 0.2 or less.

[0017] Conductive pastes that contain a large amount of binder tend to shrink easily when drying. Large changes in the volume of the conductive paste cause shrinkage stress in the conductive layer. As a result, cracks may occur in the separator layer adjacent to the conductive layer. Cracks in the separator layer can cause short circuits. When the mass ratio of binder to conductive material is 0.2 or less, cracks tend not to occur easily in the separator layer. This is thought to be because the volume change of the conductive paste is small.

[0018] 7. In the battery according to any one of the above items "1" to "6," the conductive layer may not contain a positive electrode active material.

[0019] As long as the conductive layer has a different composition from the positive electrode mixture, the conductive layer may contain a positive electrode active material. However, in general, the positive electrode active material is more expensive than the conductive material. By not including the positive electrode active material in the conductive layer, it is expected that the manufacturing cost can be reduced.

[0020] 8. In the battery according to any one of the above items "1" to "7", a conductive layer may be disposed so as to cover the first opening or the second opening.

[0021] In the battery described in "8" above, a positive electrode current collector may be disposed on either the first end face or the second end face.

[0022] 9. In the battery according to any one of the above items "1" to "7", a conductive layer may be disposed so as to cover the first opening and the second opening.

[0023] In the battery described in "9" above, a positive electrode current collector may be disposed on both the first end surface and the second end surface. The increase in current collection area is expected to reduce the battery resistance.

[0024] 10. In a method for manufacturing a battery according to one aspect of the present disclosure, a battery is manufactured using a honeycomb structure as a substrate. The honeycomb structure includes a first end face, a second end face, and a side wall. The second end face is the face opposite the first end face. The side wall connects the first end face and the second end face. A plurality of through holes are formed extending from the first end face to the second end face. Each of the through holes has a first opening that opens to the first end face and a second opening that opens to the second end face. The method for producing a battery includes the following steps (a) to (e) in this order: (a) The negative electrode mixture is formed into a honeycomb structure. (b) At least a portion of the inner wall of the through hole is covered with a separator layer. (c) A positive electrode mixture is disposed inside the through hole by forcing the positive electrode paste into the through hole from the first opening or the second opening. (d) A conductive paste is applied to at least one of the first opening and the second opening to form a conductive layer in contact with the positive electrode mixture. (e) A positive electrode current collector is adhered to the conductive layer from the outside of the through hole. The negative electrode mixture includes a negative electrode active material. The positive electrode mixture includes a positive electrode active material. The conductive layer includes a conductive material. The conductive layer has a different composition from the positive electrode mixture.

[0025] 11. In the method for producing a battery according to the above item "10," a positive electrode paste may be forced into the through-hole from the first opening. Also, a conductive paste may be applied to at least the second opening to form a conductive layer.

[0026] Compared to the side where the positive electrode paste was pushed in (the inlet side), the outlet side is more likely to have poor electrical conduction between the positive electrode composite and the positive electrode current collector. This is thought to be because the positive electrode paste is more likely to shrink on the outlet side when it dries. By arranging a conductive layer at least on the outlet side, it is expected that the battery resistance will be reduced.

[0027] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present embodiment") will be described. However, the present embodiment and the present embodiment do not limit the technical scope of the present disclosure. The present embodiment and the present embodiment are illustrative in all respects. The present embodiment and the present embodiment are non-restrictive. The technical scope of the present disclosure encompasses all modifications within the meaning and scope equivalent to the description of the claims. For example, it is originally intended that any configuration may be extracted from the present embodiment and the present embodiment, and that they may be arbitrarily combined. [Brief description of the drawings]

[0028] [Figure 1] FIG. 1 is an explanatory diagram of a problem according to one aspect of the present disclosure. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a battery according to this embodiment. [Diagram 3] FIG. 3 is a schematic diagram of a power generating element in this embodiment. [Figure 4] FIG. 4 is a schematic diagram showing an example of the negative electrode mixture in this embodiment. [Diagram 5]FIG. 5 is a schematic cross-sectional view of the power generating element in this embodiment. [Figure 6] FIG. 6 is a schematic flow chart of the battery manufacturing method in this embodiment. [Figure 7] FIG. 7 is a first optical microscope photograph showing the manufacturing process of the battery in this example. [Figure 8] FIG. 8 is a second optical microscope photograph showing the manufacturing process of the battery in this example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] <Terms and definitions> The words "comprise," "include," "have," and variations thereof (e.g., "consisting of") are open-ended. The open-ended form may or may not include additional elements in addition to the required elements. The words "consisting of" are closed-ended. However, the closed form does not exclude additional elements that are normally associated with the technology or that are unrelated to the technology disclosed. The words "consisting essentially of..." are semi-closed. The semi-closed form allows for the addition of elements that do not substantially affect the basic and novel characteristics of the technology disclosed.

[0030] "At least one of A and B" includes "A or B" as well as "A and B." "At least one of A and B" can also be written as "A and / or B."

[0031] Expressions such as "may" and "may" are used in the permissive sense, meaning "to have the possibility," rather than in the obligatory sense, meaning "to have to."

[0032] Geometric terms (e.g., "parallel," "perpendicular," "orthogonal," etc.) should not be interpreted in a strict sense. For example, "parallel" may deviate slightly from the strict meaning of "parallel." Geometric terms may include, for example, tolerances, errors, etc. in design, work, manufacturing, etc. The dimensional relationships in each drawing may not match the actual dimensional relationships. To aid the reader's understanding, the dimensional relationships (length, width, thickness, etc.) in each drawing may be changed. Furthermore, some configurations may be omitted.

[0033] Numerical ranges such as "m to n%" include the upper and lower limits unless otherwise specified. That is, "m to n%" indicates a numerical range of "m% or more and n% or less". Furthermore, "m% or more and n% or less" includes "more than m% and less than n%". Furthermore, a numerical value arbitrarily selected from within the numerical range may be set as a new upper or lower limit. For example, a new numerical range may be set by arbitrarily combining a numerical value within the numerical range with a numerical value described in another part of this specification, in a table, in a figure, or the like.

[0034] All numerical values ​​are modified by the term "about." The term "about" may mean, for example, ±5%, ±3%, ±1%, etc. All numerical values ​​may be approximations that may vary depending on the application of the disclosed technology. All numerical values ​​may be expressed with significant figures. Measurements may be average values ​​of multiple measurements. The number of measurements may be three or more, five or more, or ten or more. In general, the more measurements are taken, the more reliable the average value is expected to be. Measurements may be rounded off based on the number of significant figures. Measurements may include errors associated with, for example, the detection limits of the measuring device.

[0035] When a compound is expressed by a stoichiometric composition formula (e.g., "LiCoO2", etc.), the stoichiometric composition formula is merely a representative example of the compound. The compound may have a non-stoichiometric composition. For example, when lithium cobalt oxide is expressed as "LiCoO2", unless otherwise specified, the lithium cobalt oxide is not limited to the composition ratio of "Li / Co / O=1 / 1 / 2" and may contain Li, Co, and O in any composition ratio. Furthermore, doping, substitution, etc. with trace elements may also be allowed.

[0036] "Sphere equivalent diameter" refers to the diameter of a sphere having the same volume as the volume of an object. The volumes of 30 objects (e.g., 30 particles) are measured. The volume of an object can be determined, for example, by measuring the dimensions of a representative portion in a microscope image. For example, in the case of a cylinder (round rod), the diameter (thickness) and height (length) can be measured. The average volume (arithmetic mean) of the 30 objects is calculated. The sphere equivalent diameter is calculated using the following formula. φ=2{(V / π)(3 / 4)} 1 / 3 φ: Ball equivalent diameter V: average volume of the object π: Pi

[0037] The "average particle size" refers to the particle size at which the cumulative frequency from the small particle size side reaches 50% in the volume-based particle size distribution. The average particle size is also written as "D50". The average particle size can be measured by a laser diffraction method.

[0038] The "positive electrode current collector" refers to a member that transfers electrons between the positive electrode mixture and the positive electrode current collector. The positive electrode current collector may be connected to an external terminal (positive electrode terminal). The positive electrode current collector may also function as an external terminal. The same applies to the negative electrode current collector.

[0039] An application example to a "lithium ion battery" will be described below. However, the lithium ion battery is merely one example of a battery. The present embodiment can be applied to any battery system.

[0040] <Battery> FIG. 2 is a schematic diagram showing an example of a battery in this embodiment. Hereinafter, "the battery in this embodiment" may be abbreviated as "this battery". This battery 100 includes a power generating element 50 and a positive electrode current collector 25. This battery 100 may further include, for example, a negative electrode current collector 15, an electrolyte (not shown), an exterior body (not shown), and the like. The exterior body may house the power generating element 50. The exterior body may be, for example, a metal container or a pouch made of a metal foil laminate film. The power generating element 50 may be impregnated with the electrolyte.

[0041] 3 is a schematic diagram of a power generating element in this embodiment. The power generating element 50 has a honeycomb structure as a base material. The power generating element 50 includes a negative electrode mixture 10 (honeycomb structure), a positive electrode mixture 20, a separator layer 30, and a conductive layer 40 (see FIG. 5).

[0042] 《Negative electrode mixture》 The negative electrode mixture 10 includes a negative electrode active material. The negative electrode active material may be a particle group. The negative electrode active material may have an average particle diameter of, for example, 1 to 30 μm. The negative electrode mixture may further include, for example, a conductive material, a binder, and the like. The negative electrode mixture 10 may include, for example, 1 to 10% of a binder, 0 to 10% of a conductive material, and the balance of the negative electrode active material, in mass fraction. The negative electrode active material may include any component. The negative electrode active material may include, for example, at least one selected from the group consisting of natural graphite, artificial graphite, soft carbon, hard carbon, silicon, silicon oxide, tin, tin oxide, and lithium titanate. The conductive material may include, for example, acetylene black (AB), carbon nanotubes (CNT), and the like. The binder may include, for example, styrene butadiene rubber (SBR), carboxymethyl cellulose (CMC), and the like.

[0043] 4 is a schematic diagram showing an example of the negative electrode composite material in this embodiment. The negative electrode composite material 10 is molded into a predetermined shape. The molded body may be porous. The negative electrode composite material 10 may have any outer shape. The outer shape of the negative electrode composite material 10 may be, for example, columnar, plate-like, or the like. The outer shape of the negative electrode composite material 10 may be, for example, cylindrical, prismatic, or the like.

[0044] The negative electrode mixture 10 may have, for example, a diameter 10d. The diameter 10d indicates the maximum width in the XY plane. The diameter 10d may be, for example, 1 to 1000 mm. The negative electrode mixture 10 may have, for example, a height 10h. The height 10h indicates the maximum width in the YZ plane. The height 10h may be, for example, 1 to 1000 mm. The ratio of the height 10h to the diameter 10d may be, for example, 0.1 to 10.

[0045] The negative electrode composite material 10 forms a honeycomb structure. The "honeycomb structure" may also be expressed as, for example, a "honeycomb core" or a "honeycomb molded body". The honeycomb structure (negative electrode composite material 10) includes a first end face 11, a second end face 12, and a side wall 13. The second end face 12 is the opposite face of the first end face 11. The second end face 12 may be parallel to the first end face 11 or may be non-parallel. The first end face 11 and the second end face 12 may each independently be a flat surface or a curved surface. The side wall 13 connects the first end face 11 and the second end face 12. The side wall 13 is formed over the entire periphery of the first end face 11 and the second end face 12. For example, a negative electrode current collector 15 may be joined to the side wall 13 (see FIG. 2 and FIG. 5). The negative electrode current collector 15 may include, for example, a metal foil, a metal plate, a metal wire, etc. The negative electrode current collector 15 may include, for example, Cu, Ni, stainless steel, etc.

[0046] A plurality of through holes 2 are formed in the negative electrode composite material 10. Each of the through holes 2 extends from a first end face 11 to a second end face 12. The direction in which the through holes 2 extend may be parallel to the axial direction (Z-axis direction) of the negative electrode composite material 10. In a cross section perpendicular to the axial direction (XY plane), the through holes 2 may be arranged regularly or irregularly. In the XY plane, the through holes 2 may be arranged at a density of, for example, 0.1 to 10 holes / mm 2 The through holes 2 may be formed at a density of 0.1 to 1.0 mm. In the XY plane, the cross-sectional shape of the through holes 2 is arbitrary. The cross-sectional shape may be, for example, a circular shape or a polygonal shape. The cross-sectional shape may be, for example, a triangular to dodecagonal shape. The cross-sectional shape may be, for example, a square shape or a regular hexagonal shape.

[0047] The walls (parts of the negative electrode composite material 10) separating the through holes 2 from each other are also called "ribs." In the XY plane, the ribs may extend, for example, in a mesh pattern. The ribs may have a thickness of, for example, 100 to 300 μm.

[0048] <Separator layer> 5 is a schematic cross-sectional view of the power generating element in this embodiment. The separator layer 30 covers at least a part of the inner wall of the through-hole 2. The separator layer 30 is interposed between the negative electrode mixture 10 and the positive electrode mixture 20. The separator layer 30 separates the positive electrode mixture 20 from the negative electrode mixture 10. The separator layer 30 has Li ion permeability. The separator layer 30 may be, for example, porous. The separator layer 30 may be permeated with an electrolyte.

[0049] The separator layer 30 may have a thickness of, for example, 10 to 100 μm. The separator layer 30 includes an insulating material. The separator layer 30 may include, for example, ceramic particles, resin particles, polymer gel, solid electrolyte, etc. The separator layer 30 may include, for example, boehmite, polyvinylidene fluoride (PVDF), polyimide (PI), sulfide solid electrolyte (Li3PS4), etc.

[0050] The separator layer 30 may extend so as to cover at least one of the first end face 11 and the second end face 12, for example. The separator layer 30 may have a partially different composition. For example, the composition of the separator layer 30 may be different between the inside and the outside of the through hole 2. For example, the composition of the separator layer 30 may be different between the portion covering the inner wall of the through hole 2 and the portion covering the first end face 11 (or the second end face 12). For example, the portion covering the inner wall of the through hole 2 may contain a ceramic particle group. For example, the portion covering the first end face 11 (or the second end face 12) may contain a resin particle group.

[0051] <Positive electrode mixture> The positive electrode mixture 20 includes a positive electrode active material. The positive electrode active material may be a particle group. The positive electrode active material may have an average particle diameter of, for example, 1 to 30 μm. The positive electrode mixture 20 may further include, for example, a conductive material, a binder, and the like. The positive electrode mixture 20 may include, for example, 1 to 10% of a binder, 1 to 10% of a conductive material, and the remainder of the positive electrode active material, in mass fraction.

[0052] The positive electrode active material may include any component. The positive electrode active material may include at least one selected from the group consisting of lithium cobalt oxide, lithium nickel oxide, lithium manganate, lithium nickel cobalt manganate, lithium nickel cobalt aluminate, and lithium iron phosphate. The conductive material may include, for example, AB, etc. The binder may include, for example, PVDF, etc.

[0053] The positive electrode mixture 20 is disposed inside the through-hole 2. The positive electrode mixture 20 may be porous. The positive electrode mixture 20 may be filled inside the through-hole 2. The positive electrode mixture 20 may be, for example, columnar. The positive electrode mixture 20 may fill the through-hole 2 without any gaps. A part of the through-hole 2 may remain unfilled. The positive electrode mixture 20 may be layered. The positive electrode mixture 20 may be laminated on the separator layer 30. The positive electrode mixture 20 may extend along the inner wall of the through-hole 2. For example, in the XY plane, the positive electrode mixture 20, the separator layer 30, and the negative electrode mixture 10 may be concentrically disposed.

[0054] The positive electrode mixture 20 may include a depression 21 (see FIG. 1). The depression 21 recedes from the first opening 2a or the second opening 2b toward the inside of the through hole 2. The depression 21 may be formed by the contraction of the positive electrode paste 4 when the positive electrode paste 4 dries. The depression 21 may be, for example, in a cone shape. The depth of the depression 21 may be, for example, 0.1 to 1 times, or 0.1 to 0.5 times, the diameter of the through hole 2.

[0055] Conductive Layer The conductive layer 40 includes a conductive material. The conductive layer 40 may further include, for example, a binder, a positive electrode active material, and the like. However, the conductive layer 40 has a different composition from the positive electrode mixture 20. The mass fraction of the positive electrode active material in the conductive layer 40 is lower than the mass fraction of the positive electrode active material in the positive electrode mixture 20. The conductive layer 40 may not include a positive electrode active material. The conductive layer 40 may include, for example, 0.1 to 30% by mass of a binder and the remainder being a conductive material. The mass fraction of the binder may be, for example, 1 to 20%, or 5 to 15%.

[0056] The weight ratio of the binder to the conductive material may be, for example, 0.2 or less. By having a weight ratio of the binder to the conductive material of 0.2 or less, cracks in the separator layer 30 may be reduced. The weight ratio of the binder to the conductive material may be, for example, 0.1 or less. The weight ratio of the binder to the conductive material may be, for example, greater than 0.01, 0.07 or more, or 0.1 or more.

[0057] The conductive material has electronic conductivity. The conductive material may contain at least one selected from the group consisting of, for example, spherical carbon particles, disk-shaped carbon particles, and rod-shaped carbon particles. An example of the spherical carbon particles is, for example, spheroidized graphite. An example of the rod-shaped carbon particles is, for example, carbon fiber such as milled fiber. In particular, when the conductive material contains rod-shaped carbon particles, a reduction in battery resistance is expected. This is believed to be because the rod-shaped carbon particles can form an electron conduction path over a long distance. The rod-shaped carbon particles may have an average length (fiber length) of, for example, 50 to 500 μm, 150 to 250 μm, or 100 to 200 μm. The rod-shaped carbon particles may have an average diameter (fiber diameter) of, for example, 1 to 30 μm, or 5 to 15 μm.

[0058] The conductive material may have a sphere-equivalent diameter of 10 μm or more. When the sphere-equivalent diameter is 10 μm or more, the conductive material tends to be less likely to penetrate into the separator layer 30. The sphere-equivalent diameter may be, for example, 11 μm or more, 20 μm or more, or 24 μm or more. The sphere-equivalent diameter may be, for example, 38 μm or less, or 30 μm or less.

[0059] The conductive layer 40 connects the positive electrode composite material 20 inside the through hole 2 and the positive electrode current collector 25 outside the through hole 2. For example, the conductive layer 40 may be arranged so as to block at least one of the first opening 2a and the second opening 2b. For example, the conductive layer 40 may be arranged so as to block one of the first opening 2a or the second opening 2b. For example, the conductive layer 40 may be arranged so as to block both the first opening 2a and the second opening 2b. For example, the conductive layer 40 may extend so as to cover a part of the separator layer 30. For example, the conductive layer 40 may extend so as to cover the entire first end face 11. For example, the conductive layer 40 may extend so as to cover the entire second end face 12.

[0060] 《Positive electrode current collector》 The positive electrode current collector 25 is disposed outside the through-hole 2. The positive electrode current collector 25 may be disposed on either the first end face 11 or the second end face 12. The positive electrode current collector 25 may be disposed on both the first end face 11 and the second end face 12. The positive electrode current collector 25 may be bonded to the conductive layer 40. The positive electrode current collector 25 may include, for example, a metal foil, a metal plate, a metal wire, or the like. The positive electrode current collector 25 may include, for example, Al, an Al alloy, stainless steel, or the like. The positive electrode current collector 25 may have a thickness of, for example, 5 to 50 μm.

[0061] 《Electrolyte》 The battery 100 may include an electrolytic solution. The electrolytic solution includes a supporting electrolyte and a solvent. The supporting electrolyte is dissolved in the solvent. The supporting electrolyte may include any component. The supporting electrolyte may include at least one selected from the group consisting of LiPF6, LiBF4, and Li(FSO2)2N. The concentration of the supporting electrolyte may be, for example, 0.5 to 2 mol / kg.

[0062] The solvent is aprotic. The solvent may contain any component. The solvent may contain at least one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC) and diethyl carbonate (DEC). The electrolyte may further contain any additive in addition to the supporting electrolyte and the solvent.

[0063] <Battery manufacturing method> FIG. 6 is a schematic flow chart of the manufacturing method of the battery in this embodiment. Hereinafter, the "manufacturing method of the battery in this embodiment" may be abbreviated as "the present manufacturing method". The present manufacturing method includes "(a) forming a honeycomb structure", "(b) forming a separator layer", "(c) disposing a positive electrode composite material", "(d) forming a conductive layer", and "(e) disposing a positive electrode current collector". The present manufacturing method may further include, for example, "(f) pouring liquid" or the like.

[0064] (a) Forming of honeycomb structure The method includes forming the negative electrode mixture into a honeycomb structure. For example, the negative electrode mixture may be formed by extrusion.

[0065] For example, the negative electrode paste is prepared by dispersing the negative electrode mixture in a dispersion medium. For example, an appropriate dispersion medium can be selected depending on the type of binder, etc. The dispersion medium may contain, for example, water, N-methyl-2-pyrrolidone (NMP), butyl butyrate, tetralin, etc. The same applies to the pastes described below.

[0066] A mold is prepared. The mold has an extrusion port (die). The extrusion port corresponds to the shape of the honeycomb structure. The negative electrode paste is extruded from the extrusion port to form a green body. The green body is dried to form the honeycomb structure.

[0067] (b) Formation of Separator Layer The present manufacturing method includes covering at least a portion of the inner wall of the through-hole 2 with a separator layer 30. The separator layer 30 may be formed by, for example, a suction method.

[0068] For example, a separator paste is prepared by dispersing an insulating material and a binder in a dispersion medium. The separator paste is sucked from the first opening 2a or the second opening 2b, so that the separator paste can adhere to the inner wall of the through hole 2. For example, the separator paste may be sucked by a vacuum pump. The separator paste is dried, so that the separator layer 30 can be formed.

[0069] A separator layer 30 may also be formed on the first end surface 11 and the second end surface 12. For example, an insulating material may be applied to the first end surface 11 and the second end surface 12 by electrodeposition.

[0070] (c) Arrangement of positive electrode composite material This manufacturing method includes disposing positive electrode mixture 20 inside through hole 2 by forcing positive electrode paste 4 into through hole 2 from first opening 2a or second opening 2b.

[0071] For example, a positive electrode mixture is dispersed in a dispersion medium to prepare a positive electrode paste 4. For example, the positive electrode paste 4 and a honeycomb structure are placed in a cylinder. In the cylinder, the positive electrode paste 4 may be pressed into the through-hole 2 by a piston. The positive electrode paste is dried to place a positive electrode mixture 20 in the through-hole 2.

[0072] The positive electrode paste 4 is filled into the through-hole 2 from the first opening 2a or the second opening 2b. In FIG. 1, as an example, the positive electrode paste 4 is inserted from the first opening 2a. For example, a porous filter 200 may be disposed on the outlet side (the second opening 2b side). The porous filter 200 may have a mesh size that allows the dispersion medium to pass through and does not allow the solid content (such as the positive electrode active material) to pass through. The porous filter 200 may be, for example, a metal mesh, a porous body, or the like. By disposing the porous filter 200 on the outlet side, it is expected that the positive electrode mixture 20 will be densely filled.

[0073] (d) Formation of Conductive Layer This manufacturing method includes applying a conductive paste to at least one of the first opening 2a and the second opening 2b to form a conductive layer 40. The conductive layer 40 is formed so as to be in contact with the positive electrode composite material 20 inside the through hole 2.

[0074] For example, a conductive paste is prepared by dispersing a conductive material and a binder in a dispersion medium. The conductive paste may be applied so as to cover at least one of the first opening 2a and the second opening 2b. For example, the conductive paste may be applied to at least one of the first end surface 11 and the second end surface 12. The conductive paste may be dried to form the conductive layer 40.

[0075] For example, when the positive electrode paste 4 is being pushed in through the first opening 2a (i.e., when the first opening 2a is the inlet side), the conductive paste may be applied to at least the second opening 2b (the outlet side) because the positive electrode paste 4 is likely to shrink on the outlet side.

[0076] (e) Arrangement of positive electrode current collector This manufacturing method includes bonding the positive electrode current collector 25 to the conductive layer 40 from the outside of the through-hole 2. The positive electrode current collector 25 can be bonded to the conductive layer 40 by any method. For example, the positive electrode current collector 25 may be pressure-bonded to the conductive layer 40. For example, the positive electrode current collector 25 may be bonded to the conductive layer 40 by a conductive paste.

[0077] The present manufacturing method may include joining the negative electrode current collector 15 to the negative electrode composite material 10. For example, a sheet-shaped negative electrode current collector 15 may be attached to the side wall 13 of the honeycomb structure. For example, a linear negative electrode current collector 15 may be wound around the side wall 13 of the honeycomb structure.

[0078] (f) Injection This manufacturing method may include permeating the separator layer 30 with an electrolytic solution. For example, an exterior body (not shown) is prepared. The power generating element 50 is housed in the exterior body. The electrolytic solution is injected into the exterior body. After the electrolyte solution is injected, the exterior body is sealed. The electrolytic solution is allowed to permeate the separator layer 30. In this manner, the present battery 100 can be manufactured. EXAMPLES

[0079] <Production of test batteries> Test batteries No. 1 to 14 were produced as follows. Hereinafter, for example, "test battery No. 1" may be abbreviated as "No. 1."

[0080] No.1 (a) Forming of honeycomb structure The following materials were prepared: Negative electrode active material: natural graphite (average particle size: 15 μm) Binder: CMC Dispersion medium: Ion-exchanged water

[0081] A negative electrode paste was prepared by mixing 100 parts by mass of a negative electrode active material, 10 parts by mass of a binder, and 60 parts by mass of a dispersion medium. The negative electrode paste was extruded from a mold to form a molded body. The molded body was dried at 120°C for 3 hours to form a honeycomb structure. The honeycomb structure had the following structure.

[0082] Shape: Cylindrical (diameter: 20 mm, height: 10 mm) Arrangement of through holes: equally spaced, regular (honeycomb) Cross-sectional shape of through hole: regular hexagon (length of one side: 700 μm, rib thickness: 200 μm)

[0083] (b) Formation of the separator layer The following materials were prepared: Insulating material: Boehmite (average particle size: 0.5 μm) Binder: PVDF (product name KF Polymer, grade #8500, manufactured by Kureha Corporation) Dispersion medium: NMP

[0084] A separator paste was prepared by mixing 57 parts by mass of an insulating material, 5 parts by mass of a binder, and 38 parts by mass of a dispersion medium. 3 to 5 g of the separator paste was placed on a first end face of a honeycomb structure. A vacuum pump sucked the separator paste into the through holes from the second end face side. This caused the separator paste to adhere to the inner walls of the through holes. The honeycomb structure was dried at 120°C for 15 minutes. This resulted in the formation of a separator layer (boehmite layer). The average thickness of the separator layer was measured by observation with an optical microscope. The average thickness was 65 μm.

[0085] An electrocoating paint (product name "Elecoat PI", manufactured by Shimizu Corporation) was prepared. The electrocoating paint contained an insulating material (polyimide) and a dispersion medium (water). A Ni flat wire (thickness: 50 μm, width: 3 mm) was prepared. The Ni flat wire was wound around the side wall of the honeycomb structure. The Ni flat wire was connected to a power source. The honeycomb structure was immersed in the electrocoating paint. A voltage of 30 V was applied for 2 minutes, with the honeycomb structure (negative electrode composite material) as the cathode and the working electrode as the anode. As a result, the first end face and the second end face were covered with the separator layer (polyimide layer). After the electrocoating, the honeycomb structure was lightly washed with water to remove excess electrocoating paint. After washing, the honeycomb structure was heat-treated at 180°C for 1 hour.

[0086] (c) Arrangement of positive electrode composite The following materials were prepared: Positive electrode active material: Lithium cobalt oxide (average particle size: 10 μm) Conductive material: Acetylene black Binder: PVDF (product name: KF Polymer, grade #1300, manufactured by Kureha Corporation) Dispersion medium: NMP

[0087] A positive electrode paste was prepared by mixing 64 parts by mass of a positive electrode active material, 4 parts by mass of a conductive material, 2 parts by mass of a binder, and 30 parts by mass of a dispersion medium. A plastic pipe was prepared. The pipe had an inlet end and an outlet end. A honeycomb structure was fixed to the outlet end side. A plate-shaped metal filter was prepared. The pipe was fixed upright on the metal filter. The outlet end was in contact with the metal filter. 3.5 g of positive electrode paste was injected from the inlet end of the pipe. A cylinder (round bar) was inserted into the pipe from the inlet end. The cylinder had a diameter (body diameter) approximately the same as the inner diameter of the pipe. The cylinder was pressed with a pressing force of 300 N. This forced the positive electrode paste into the through hole. When the pressing force exceeded 500 N, the pressing of the cylinder was stopped. The honeycomb structure was removed from the pipe. The honeycomb structure was vacuum dried at 120° C. for 30 minutes. As a result, the positive electrode mixture was disposed inside the through-hole.

[0088] Fig. 7 is a first optical microscope photograph showing the manufacturing process of the battery in this example. Fig. 7 shows a cross section (opening and its periphery) of the honeycomb structure after the positive electrode paste is dried. Since the positive electrode paste shrinks during drying, a depression 21 is formed at the tip of the positive electrode mixture 20.

[0089] (d) Formation of a conductive layer The following materials were prepared: Conductive material: Rod-shaped carbon particles (average length: 100 μm, average diameter: 10 μm, equivalent sphere diameter: 30 μm) Binder: PVDF (product name: KF Polymer, grade #1300, manufactured by Kureha Corporation) Dispersion medium: NMP

[0090] A conductive paste was prepared by mixing 70 parts by mass of a conductive material, 7 parts by mass of a binder, and 23 parts by mass of a dispersion medium. The conductive paste was applied to both the first end face and the second end face. The conductive paste was applied by pressing with a spatula. The conductive paste was then shaped with the spatula so as to be smooth. After the conductive paste was applied, the honeycomb structure was vacuum dried at 120°C for 30 minutes. This formed a conductive layer.

[0091] 8 is a second optical microscope photograph showing the manufacturing process of the battery in this Example. A conductive layer 40 is formed so as to fill the recess 21 (FIG. 7).

[0092] Insulation Test The DC resistance was measured between the conductive layer and the side wall of the honeycomb structure (exposed portion of the negative electrode composite material) using a tester. In Table 1 below, "pass" indicates that the DC resistance (insulation resistance) was 1 MΩ or more. "fail" indicates that the DC resistance was less than 1 MΩ. In the samples with a result of "pass", the DC resistance exceeded the measurement limit of the tester.

[0093] (e) Arrangement of positive electrode current collector Two sheets of Al foil (diameter: 15 mm, thickness: 15 μm) were prepared as positive electrode current collectors. The positive electrode current collectors were bonded to the conductive layers using the conductive paste used to form the conductive layers. The positive electrode current collectors were bonded to both the conductive layers on the first end surface and the conductive layers on the second end surface. After the positive electrode current collectors were placed, the honeycomb structure was dried at 120° C. for 15 minutes.

[0094] Arrangement of negative electrode current collector A Ni flat wire (thickness: 50 μm, width: 3 mm) was prepared as a negative electrode current collector. The negative electrode current collector was wound around the side wall (outer peripheral surface) of the honeycomb structure in one revolution.

[0095] Stainless steel lead tabs were prepared as external terminals. The lead tabs were welded to the positive electrode current collector and the negative electrode current collector, respectively. In this manner, a power generating element was formed.

[0096] (f) Injection A pouch made of an aluminum laminate film was prepared as an exterior body. A power generating element was housed in the exterior body. 5 g of an electrolyte was injected into the exterior body. After the electrolyte was injected, the exterior body was vacuum sealed. The electrolyte had the following composition. A test battery was manufactured as described above.

[0097] Electrolyte composition Supporting electrolyte: LiPF6 (concentration: 1mol / kg) Solvent: EC / EMC / DMC=1 / 1 / 1 (volume ratio)

[0098] Battery resistance measurement Charge, rest, and discharge were performed in sequence under the following conditions: "CC" stands for constant current method, "CV" stands for constant voltage method, and "CCCV" stands for constant current-constant voltage method.

[0099] Charging: CCCV, CC current = 40mA, CV voltage = 4.2V, final current = 10mA Pause: 10 minutes Discharge: CCCV, CC current = 40mA, CV voltage = 3V, final current = 10mA

[0100] After the initial charge and discharge, the voltage of the test battery was adjusted according to the following conditions. Charging: CCCV, CC current = 40mA, CV voltage = 3.85V, final current = 10mA

[0101] After adjusting the voltage, the test battery was discharged for 1 second with a CC current of 200 mA. The voltage drop 1 second after the start of discharge was measured. The battery resistance was calculated from the voltage drop and the discharge current.

[0102] No.2 A test battery was fabricated in the same manner as No. 1, except that rod-shaped carbon particles (average length: 200 μm, equivalent spherical diameter: 38 μm) were used as the conductive material.

[0103] No.3 A test battery was fabricated in the same manner as No. 1, except that rod-shaped carbon particles (average length: 50 μm, equivalent spherical diameter: 24 μm) were used as the conductive material.

[0104] No.4, 5, 12~13 Test cells were fabricated similarly to No. 1, except that the weight ratio of binder to conductive material in the conductive paste (see Table 1 below) was varied.

[0105] No.6 A test battery was manufactured in the same manner as No. 1, except that spherical carbon particles (spheroidized graphite, average particle size: 20 μm, equivalent sphere size: 20 μm) were used as the conductive material instead of the rod-shaped carbon particles.

[0106] No.7 A test battery was manufactured in the same manner as No. 1, except that spherical carbon particles (spheroidized graphite, average particle size: 11 μm, equivalent sphere size: 11 μm) were used as the conductive material instead of the rod-shaped carbon particles.

[0107] No.8 A test battery was manufactured in the same manner as No. 1, except that the conductive paste was applied only to the first end face. That is, the conductive layer was formed only in the first opening among the first and second openings. In this example, the positive electrode paste was pushed in from the first opening. Therefore, the first opening is the inlet side (insertion side), and the second opening is the outlet side.

[0108] No.9 A test battery was fabricated in the same manner as No. 1, except that the conductive paste was applied only to the second end face, i.e., the conductive layer was formed only on the second opening (outlet side) of the first and second openings.

[0109] No.10 A test battery was fabricated similarly to No. 1, except that no conductive layer was formed and the positive electrode current collector was directly attached to the first end surface and the second end surface.

[0110] No.11 A test battery was manufactured in the same manner as No. 4, except that an amorphous carbon material (carbon black, equivalent sphere diameter: less than 1 μm) was used as the conductive material instead of the rod-like carbon particles.

[0111] No.14 The mass ratio of the binder to the conductive material in the conductive paste was changed to 0.01, and the conductive paste was applied. However, it was difficult to form a conductive layer. 4 In , production of test batteries was discontinued.

[0112] [Table 1]

[0113] <Result> There is a tendency for the battery resistance to be significantly reduced by the formation of a conductive layer between the positive electrode mixture and the positive electrode current collector (see Nos. 1 to 10 in Table 1 above).

[0114] As the sphere-equivalent diameter becomes smaller, there is a tendency for the insulation resistance to decrease (see No. 1 and 11 in Table 1 above). This is thought to be because the conductive material penetrates into the separator layer, forming a short circuit path.

[0115] As the mass ratio of binder to conductive material increases, there is a tendency for the insulation resistance to decrease (see No. 1, 13, and 14 in Table 1 above). This is thought to be because contraction stress occurs when the conductive paste dries, which can cause cracks in the separator layer.

[0116] Compared to when spherical carbon particles are used, when rod-shaped carbon particles are used, the battery resistance tends to be reduced (see Nos. 1 to 3, 6, and 7 in Table 1 above). This is believed to be because the rod-shaped carbon particles can form a long-distance conductive path.

[0117] Samples with conductive layers on both the inlet side (first opening) and the outlet side (second opening) tend to have a greater effect in reducing battery resistance than samples with conductive layers on either the inlet side or the outlet side (see Nos. 1, 8, and 9 in Table 1 above).

[0118] The samples with the conductive layer on the outlet side tend to have a greater effect on reducing battery resistance than the samples with the conductive layer on the inlet side (see No. 8 and 9 in Table 1 above). This is thought to be because the positive electrode paste is more likely to shrink on the outlet side when drying. [Explanation of symbols]

[0119] 2 through hole, 2a first opening, 2b second opening, 4 positive electrode paste, 10 negative electrode composite, 10d diameter, 10h height, 11 first end surface, 12 second end surface, 13 side wall, 15 negative electrode current collector, 20 positive electrode composite, 21 depressed portion, 25 positive electrode current collector, 30 separator layer, 40 conductive layer, 50 power generating element, 100 battery, 200 porous filter.

Claims

1. A negative electrode mixture, a separator layer, a positive electrode mixture, a conductive layer, and a positive electrode current collector. Including, The negative electrode mixture contains a negative electrode active material, The negative electrode mixture forms a honeycomb structure, The honeycomb structure includes a first end face, a second end face, and a side wall, the second end surface is an opposite surface to the first end surface, the side wall connects the first end surface and the second end surface, A plurality of through holes are formed extending from the first end surface to the second end surface, Each of the through holes has a first opening that opens into the first end surface and a second opening that opens into the second end surface, the separator layer covers at least a portion of an inner wall of the through hole, the separator layer separates the positive electrode mixture from the negative electrode mixture; The positive electrode mixture contains a positive electrode active material, The positive electrode mixture is disposed inside the through hole, the conductive layer includes a conductive material; the conductive layer has a different composition from the positive electrode mixture, The conductive layer does not contain the positive electrode active material, the positive electrode current collector is disposed outside the through hole, the conductive layer connects the positive electrode mixture and the positive electrode current collector, The positive electrode mixture includes a recess, the recessed portion is recessed from the first opening or the second opening toward the inside of the through hole, The conductive material has a spherical equivalent diameter of 10 μm or more, The conductive layer further comprises a binder, a mass ratio of the binder to the conductive material is 0.07 or more and 0.2 or less; battery.

2. the conductive layer is disposed so as to cover at least one of the first opening and the second opening.

10. The battery of claim 1.

3. The conductive material includes at least one selected from the group consisting of spherical carbon particles, disk-shaped carbon particles, and rod-shaped carbon particles. The battery according to claim 1 or 2.

4. the conductive layer is disposed so as to cover the first opening or the second opening; 3. The battery of claim 2. (However, "or" does not mean either one or both in a mathematical sense.)

5. the conductive layer is disposed so as to cover the first opening and the second opening.

3. The battery of claim 2.

6. A method for manufacturing a battery using a honeycomb structure as a substrate, comprising: The honeycomb structure includes a first end face, a second end face, and a side wall, the second end surface is an opposite surface to the first end surface, the side wall connects the first end surface and the second end surface, A plurality of through holes are formed extending from the first end surface to the second end surface, Each of the through holes has a first opening that opens into the first end surface and a second opening that opens into the second end surface, (a) forming a negative electrode mixture into the honeycomb structure; (b) covering at least a portion of the inner wall of the through hole with a separator layer; (c) disposing a positive electrode composite material inside the through hole by forcing a positive electrode paste into the through hole from the first opening or the second opening; (d) applying a conductive paste to at least one of the first opening and the second opening to form a conductive layer in contact with the positive electrode mixture; and (e) adhering a positive electrode current collector to the conductive layer from the outside of the through hole; in that order, the positive electrode mixture is disposed inside the through hole so as to include a recess; the recessed portion is recessed from the first opening or the second opening toward the inside of the through hole, The negative electrode mixture contains a negative electrode active material, The positive electrode mixture contains a positive electrode active material, the conductive layer includes a conductive material; the conductive layer has a different composition from the positive electrode mixture, The conductive layer does not contain the positive electrode active material, The conductive material has a spherical equivalent diameter of 10 μm or more, The conductive layer further comprises a binder, a mass ratio of the binder to the conductive material is 0.07 or more and 0.2 or less; How batteries are manufactured.

7. The positive electrode paste is forced into the through hole from the first opening, and The conductive paste is applied to at least the second opening to form the conductive layer. A method for producing the battery according to claim 6.

Citation Information

Patent Citations

  • Secondary battery and manufacturing method thereof

    JP2019185933A

  • Secondary battery and method of manufacturing the same

    JP2020123484A

  • Battery and manufacturing method of the same

    JP2022014066A